BRAIN FOG IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE, AND ASSOCIATION WITH USE OF PROBIOTICS. (22nd January 2022) - Dadlani, Apaar; Gala, Khushboo; Rai, Jayesh; Rai, Shesh; Dryden, Gerald
Abstract: INTRODUCTION: Brain fog has been extensively studied in patients with inflammatory bowel disease (IBD). Probiotics have been shown to increase the incidence of brain fog in patients independently. There is a high prevalence of probiotic consumption in patients with IBD in clinical practice, whether by a physician or not. We aimed to study if there was an association between brain fog and IBD patients who took probiotics and those who did not. METHODS: We conducted a cross-sectional study of patients visiting IBD clinic. Patients over the age of 18 with a biopsy-proven diagnosis of inflammatory bowel disease, without any known pre-existing psychiatric illness or current use of opioid medications were included. They were divided into 2 groups: those with history of probiotic use and those without. Patients were given a questionnaire that included details about symptoms of brain fog. Groups were analyzed by chi-square for differences in baseline demographics, and Mann Whitney U test with repeated measures to compare outcomes between groups. A p value < 0.05 was considered statistically significant. RESULTS: Of the 66 patients included (mean age 44±2 years), 35 (53%) were female and 59 (89.4%) were Caucasian. Among these patients, 31.8% (n=21) were on probiotics as dietary supplement with majority (67%, n= 14) taking probiotics for over a year. Overall, there was trend for an association between probiotic use and brain fog in all patients (p=0.080) but no statistical significance was attained. However, brain fog was significantly associated with probiotic use among Caucasian patients (p=0.044). Furthermore, there was a statistically significant association between brain fog and male patients using probiotics (p=0.004). Duration of probiotic use was also associated with brain fog (p=0.038). CONCLUSION: Consumption of probiotics was independently associated with brain fog in men, as well as Caucasian patients with IBD respectively. Future prospective studies are warranted to examine causal relationship between probiotics and IBD-associated brain fog to guide prescription of probiotic supplements for IBD.